The 'Base Cretaceous Unconformity' in a basin-centre setting, Danish Central Graben, North Sea: A cored record of resedimentation and condensation accompanying transgression and basinal overturn. (March 2022) - Ineson, Jonathan R.; Sheldon, Emma; Dybkjær, Karen; Andersen, Claus; Alsen, Peter; Jakobsen, Finn
Abstract: A cored section (North Jens-1) in the Danish Central Graben spans the 'Base Cretaceous Unconformity' (BCU) in a seismically conformable situation in a basin-centre setting. Multidisciplinary analysis of the core revealed that the apparent simplicity of the boundary in seismic profiles at this location disguises a complex, dynamic geological history. Dark, organic-rich, laminated hemipelagic/turbiditic Farsund Formation mudstones of late Ryazanian ( Surites stenomphalus Zone) age are overlain by a thick slump sheet of upper Ryazanian mudstones, probably derived from relict rift-fault scarps on the basin floor. An erosionally-based gravity-flow bed (a hybrid density-flow deposit) of latest Ryazanian ( Peregrinoceras albidum Zone) age forms the lowermost unit of the Valhall Formation. The lower boundary of this bed may record a minor hiatus across the stenomphalus–albidum zonal boundary and represents the BCU, compatible with seismic and log data. The hybrid bed is capped by an intensely burrowed omission surface that represents the first clear indication in this basin-centre location of watermass overturn and the demise of the stratified, poorly oxygenated basin. The biostratigraphy, ichnofabric and fauna/flora of the succeeding bioturbated marlstones and marly chalks of the lower Valhall Formation ( Platylenticeras / Paratollia Zone) testify to increasingly oxygenated bottom waters and low sedimentation rates in a well-mixed, open marine, oligotrophic system; palynological data indicate that the onset of these conditions was linked to transgression. The North Jens-1 core illustrates the risk of assuming stratigraphic simplicity at the BCU surface in basin-centre, seismically conformable settings. Sedimentary reworking, already characteristic of the Farsund Formation setting, was probably exacerbated by transgressive erosion and accompanying sediment de-stabilization along the graben flanks. Highlights: Core spanning 'Base Cretaceous Unconformity' in a North Sea basinal setting records resedimentation and condensation. Biostratigraphy indicates a late Ryazanian age ( S. stenomphalus – P. albidum boundary) for the 'Base Cretaceous Unconformity'. Link indicated between late Ryazanian basinal turnover of the stratified 'Kimmeridge Clay' system and regional transgression. Hybrid density-flow bed records sediment wastage from the slope and shelf edge concurrent with transgression.